Modeling and Mining Ubiquitous Social Media International Workshops MSM 2011, Boston, MA, USA, October 9, 2011, and MUSE 2011, Athens, Greece, September 5, 2011, Revised Selected Papers - Atzmueller, Martin; Chin, Alvin; Helic, Denis; Hotho, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the joint thoroughly refereed post-proceedings of the Second International Workshop on Modeling Social Media, MSM 2011, held in Boston, MA, USA, in October 2011, and the Second International Workshop on Mining Ubiquitous and Social Environments, MUSE 2011, held in Athens, Greece, in September 2011. The 9 full papers included in the book are revised and significantly extended versions of papers submitted to the workshops. They cover a wide range of topics organized in three main themes: communities and networks in ubiquitous social media; mining approaches; and issues of user modeling, privacy and security.
Integrating Social Media Data for Community Detection -- Face-to-Face Contacts at a Conference: Dynamics of Communities and Roles -- Factors Influencing the Co-evolution of Social and Content Networks in Online Social Media -- Mining Dense Structures to Uncover Anomalous Behaviour in Financial Network Data -- Describing Locations Using Tags and Images: Explorative Pattern Mining in Social Media -- Learning and Transferring Geographically Weighted Regression Trees across Time -- Trend Cluster Based Kriging Interpolation in Sensor Data Networks -- Simulation of User Participation and Interaction in Online Discussion Groups -- Model-Driven Privacy and Security in Multi-modal Social Media UIs.
Keywords: Artificial intelligence; User interfaces (Computer systems).; Data mining; Information storage and retrieval; Architecture, Computer; Computers and civilization; Artificial Intelligence; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Computer System Implementation; Computers and Society